Speaking of information : the Library juice quotation book - Litwin, Rory (Library Juice Press, 2009)
"A compilation of quotations originally collected for the 'Quotes of the Week' section of Library Juice, an electronic magazine that dealt with philosophical and political dimensions of librarianship"--Provided by publisher.